Antioxidant Capacity-Related Preventive Effects of Shoumei (Slightly Fermented Camellia sinensis) Polyphenols against Hepatic Injury. (19th August 2020) - Yi, Ruokun; Wei, Yuxuan; Tan, Fang; Mu, Jianfei; Long, Xingyao; Pan, Yanni; Liu, Weiwei; Zhao, Xin
Abstract : Shoumei is a kind of white tea (slightly fermented Camellia sinensis ) that is rich in polyphenols. In this study, polyphenols were extracted from Shoumei. High-performance liquid chromatography (HPLC) showed that the polyphenols included mainly gallic acid, catechin, hyperoside, and sulfuretin. In an in vitro experiment, H2 O2 was used to induce oxidative damage in human normal hepatic L-02 cells. In an animal experiment, CCl4 was used to induce liver injury. The in vitro results showed that Shoumei polyphenols inhibited oxidative damage in normal hepatic L-02 cells, and the in vivo results showed that the polyphenols effectively reduced liver index values in mice with liver injury. The polyphenols also decreased aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), triglyceride (TG), total cholesterol (TC), blood urea nitrogen (BUN), nitric oxide (NO), malondialdehyde (MDA), interleukin 6 (IL-6), interleukin 12 (IL-12), tumour necrosis factor alpha (TNF- α ), and interferon gamma (IFN- γ ) levels and increased albumin (ALB), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) levels in the serum of mice with liver injury. Furthermore, pathological observation showed that the Shoumei polyphenols reduced CCl4 -induced hepatocyte damage. qRT-PCR and Western blotting showed that the polyphenols upregulated the mRNA and protein expression of neuronal nitric oxide synthase (nNOS), endothelial nitric oxide synthase (eNOS), manganese- (Mn-) SOD, copper/zinc- (Cu/Zn-) SOD, CAT, and inhibitor of nuclear factor kappa B (NF- κ B) alpha (I κ B- α ) and downregulated the expression of inducible nitric oxide synthase (iNOS) and NF- κ B p65. The Shoumei polyphenols had a preventive effect against CCl4 -induced mouse liver injury equivalent to that of silymarin. The four polyphenols identified as the key substances responsible for this effect mediated the effect through their antioxidant capacity. These results suggest that Shoumei polyphenols are high-quality natural products with liver-protective effects.